From Clinical Manifestations To Treatment: Understanding The Pathogenesis, Diagnostic Evaluation, Prognostic Considerations, And Management Of Acetic Acid Poisoning - Babanazarov Umid Turobkulovich (Genius Journals, 2025)
Ingestion of acetic acid can lead to a severe medical crisis characterized by tissue damage, red blood cell destruction, poisoning effects, and potential organ failure. Manifestations of this poisoning encompass intense pain, bloody vomit, breathing difficulties, and shock. A diagnosis is established through a combination of patient symptoms, laboratory analysis, and endoscopic examination. Management of acetic acid poisoning involves immediate detoxification, pain management, intravenous therapies, and ensuring the stability of essential bodily functions. Potential severe consequences include narrowing of the esophagus, kidney failure, and fatality. Preventing these incidents hinges on regulating the storage of hazardous substances and educating the public. This article will delve into the key clinical features and diagnostic markers associated with acetic acid poisoning.
Keywords: burns; hemolysis; hypersalivation